Pola Komunikasi Orang Tua dalam Menekan Dampak Negatif Konten Short Video Media Online YouTube pada Anak Usia Dini - Ni Luh Senja Harining; I Ketut Putu Suardana (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2023)
This study aims to examine the communication patterns used by parents in suppressing the negative impact of YouTube online media short video content on early childhood. The research method used is literature research which involves collecting data from various reliable sources. The results of the research show that effective communication patterns involve several important aspects. First, parents need to become active monitors of the content their children watch. They should be involved in selecting age-appropriate content and discussing it with the child. Second, parents need to guide and provide explanations about inappropriate or harmful content. They must teach children to understand the difference between comfortable and uncomfortable content. Third, parents need to build open communication and put forward a persuasive approach when dealing with inappropriate content issues. Effective communication patterns between parents and early childhood can be a powerful tool to reduce the negative impact of short video content on YouTube's online media. It is important for parents to be active monitors, provide appropriate supervision and direction, and maintain open channels of communication with their children. In doing so, they can help children develop the skills necessary to consume online media content wisely and healthily.